An Implication of Buddhist Ethical Teaching on Sustainable Development - Prakash, Gyan (Problemy Ekorozwoju, 2021)
Ethical teaching of religion has a significant impact on human action. Scripture has always been considered a guideline for human life. However, there is an argument that Buddhist philosophy is dysteleological. Therefore, it is difficult to argue for the virtuous action for protection or restore nature within the early Buddhist framework. This paper is an attempt to argue that Buddha has the main concern for Human suffering and he prescribed the solution or path to get rid of the suffering but there is a significant implication of Buddhist ethical teaching. Therefore, Buddhist ethical teaching can be a significant step towards sustainable development.